CO2/CH4 Separation in Ion-Exchanged Zeolite-like Metal Organic Frameworks with Sodalite Topology (sod-ZMOFs) - Demir, Baris; Ahunbay, M. Goktug (American Chemical Society (ACS), 2013)
In this study, the CO2/CH4 separation performance of zeolite-like metal organic frameworks (ZMOFs) with sodalite (sod) topology was evaluated via molecular simulation methods. Monte Carlo and molecular dynamic simulations were performed to estimate adsorption and diffusion selectivities both before and after the ion exchange of sod-ZMOFs with Li+, Na+, and K+ ions. For this purpose, sod-ZMOF structures that are partially or completely ion-exchanged were constructed by locating cation sites. Adsorption and diffusion selectivities were evaluated to predict permselectivities. Adsorption simulations showed that CO2 and CH4 adsorption sites in sod-ZMOFs are the same and CO2 adsorption is favored strongly over CH4 adsorption in the case of binary adsorption, due to the electrostatic interactions between the framework and CO2. Evaluation of permselectivities showed that partial-ion exchanging does not enhance the CO2 separation performance of these materials, while complete ion-exchanging increases permselectivi...
Keywords: Energy; Molecular-Dynamics; Ch4; Electronic; Temperature; Gas-Mixtures; Carbon; Coatings and Films; Co2; Surfaces; Mixed Matrix Membranes; Adsorption; Optical and Magnetic Materials; Monte-Carlo; Physical and Theoretical Chemistry; Force-Field